Application of Stem Cell Technology for Treatment of Diabetes Mellitus: Ethical Considerations - Farzaneh ZAHEDI; Bagher LARIJANI (Tehran University of Medical Sciences, 2015)
The clinical potentials of stem cells in cell-based therapies have raised great hopes in diabetes mellitus as well. However, there are complex ethical, legal, and socio-cultural issues surrounding the subject. In this paper, we intend to review in brief the main ethical issues for endocrinologists and other clinicians who are interested and work in the field of cell therapy and research.   Keywords: Cell therapy, Diabetes mellitus, Stem cell, Ethics